1995
DOI: 10.1089/aid.1995.11.249
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death Induced by HIV Type 1 Antigen Stimulation Is Associated with a Decrease in Cytotoxic T Lymphocyte Activity in Advanced HIV Type 1 Infection

Abstract: The immune competence of peripheral blood mononuclear cells (PBMCs) from human immunodeficiency virus-seropositive (HIV+) patients was studied by assessing cytotoxic T lymphocyte (CTL) activity following recall HIV antigen stimulation. Target cells were HLA-A-matched EBV-transformed B cells expressing HIV-1 antigen. In the presence of recombinant IL-2 (rIL-2, 2 or 10 U/ml), about 50% of PBMCs from HIV+ asymptomatic patients responded to HIV-1 antigen stimulation in vitro with increased cytotoxic activity. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…28,29 HIV-associated loss of V␥2V␦2 cells was postulated to involve apoptosis. 30 In this study, we found that R5 tropic HIV envelope glycoprotein induced significant death of CD4-negative V␥2V␦2 T cells.Envelope binding and signaling may be an important mechanism for depleting V␥2V␦2 cells during HIV disease. …”
mentioning
confidence: 61%
“…28,29 HIV-associated loss of V␥2V␦2 cells was postulated to involve apoptosis. 30 In this study, we found that R5 tropic HIV envelope glycoprotein induced significant death of CD4-negative V␥2V␦2 T cells.Envelope binding and signaling may be an important mechanism for depleting V␥2V␦2 cells during HIV disease. …”
mentioning
confidence: 61%